2020
DOI: 10.1177/2633105520931966
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax Protective Antigen 63 (PA63): Toxic Effects in Neural Cultures and Role in Gulf War Illness (GWI)

Abstract: Protective antigen (PA) 63 (PA63) is a protein derived from the PA83 component contained in the anthrax vaccine. The anthrax vaccine (“Biothrax”) was administered together with other vaccines to Gulf War veterans, about 35% of whom later developed a multisymptom disease (Gulf War Illness [GWI]), with prominent neurological/cognitive/mood symptoms, among others. The disease has been traditionally attributed to exposures to toxic chemicals during the war but other factors could be involved, including vaccines re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 54 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…Another issue linked to the use of toxins in therapy would be toxicity. While BoNT/A and cholera toxin B are not toxic when used properly, anthrax toxin PA might have a toxic effect as illustrated by its potential role in the Gulf War Illness, in which multi-systemic disease was first observed in Gulf War veterans vaccinated with the PA-based anthrax vaccine [ 108 ]. However, this observation needs further validation, as many other chemical or biological factors might have played a role in the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue linked to the use of toxins in therapy would be toxicity. While BoNT/A and cholera toxin B are not toxic when used properly, anthrax toxin PA might have a toxic effect as illustrated by its potential role in the Gulf War Illness, in which multi-systemic disease was first observed in Gulf War veterans vaccinated with the PA-based anthrax vaccine [ 108 ]. However, this observation needs further validation, as many other chemical or biological factors might have played a role in the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Though the brain was historically considered immuneprivileged, substantial evidence suggests that CRP and other inflammatory molecules can access the brain through several routes and influence local inflammatory pathways [36][37][38] . The source of systemic inflammation in GWI is uncertain; however, evidence increasingly points to pathogen exposure in veterans lacking specific immunity against those pathogens in contributing to GWI [39][40][41][42][43][44][45] . We have speculated that lack of immunogenetic protection against pathogens results in their persistence, and consequently promotes inflammation, autoimmunity, and ultimately neural damage 40,46 .…”
Section: Discussionmentioning
confidence: 99%
“…We have speculated that lack of immunogenetic protection against pathogens results in their persistence, and consequently promotes inflammation, autoimmunity, and ultimately neural damage 40,46 . In vitro studies have identified specific pathogens circulating in serum of veterans with GWI that contribute to harmful effects on neural cell cultures; remarkably, those damaging effects are ameliorated with the concomitant addition of antibodies [41][42][43][44] , suggesting potential avenues for intervention in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence from human [18][19][20][21] , in vitro [22][23][24][25][26] , and in silico 27 studies implicates persistent antigens stemming from lack of immunogenetic protection in GWI and GWassociated inflammation. Specifically, six Class II human leukocyte antigens (HLA), which play an essential role in host protection via antibody production, have been shown to distinguish healthy GW veterans from those with GWI, and the number of these protective HLA alleles corresponds with GWI symptom severity in a dose dependent manner 18 .…”
Section: Gwi: Lack Of Immunogenetic Protectionmentioning
confidence: 99%